2009
DOI: 10.1128/aac.00176-09
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Garenoxacin against Streptococcus pneumoniae Mutants with Characterized Resistance Mechanisms

Abstract: , and compared its potency to that of other quinolones. Garenoxacin had a significantly greater potency against pneumococci, including strains containing topoisomerase mutations. Genetic analysis of the S. pneumoniae mutants created by garenoxacin revealed that the gyrA gene was a primary target of garenoxacin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…These results further suggest that GyrA was the most crucial target for development of high-level resistance reflected in high MIC and MPC values for these three fluoroquinolones and the only target sensitive to prolonged antibiotic pressure in MPC experiments. These results are in agreement with previous findings (1,4,18,23,25,27). No clear relationship was found between the MPCs or their ratios to the MICs and the existence of gyrB, parC, or parE mutations.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…These results further suggest that GyrA was the most crucial target for development of high-level resistance reflected in high MIC and MPC values for these three fluoroquinolones and the only target sensitive to prolonged antibiotic pressure in MPC experiments. These results are in agreement with previous findings (1,4,18,23,25,27). No clear relationship was found between the MPCs or their ratios to the MICs and the existence of gyrB, parC, or parE mutations.…”
Section: Resultssupporting
confidence: 83%
“…The MPC/MIC ratio defines the concentration range in which resistant mutant subpopulations are selectively amplified, with the lower values suggesting a better ability to prevent mutant emergence (4,13,23,25). In the current study, moxifloxacin and levofloxacin MPC/MIC ratios were within the same range for most strains; Ͼ80% of strains had ratios of 2 to 4.…”
Section: Resultsmentioning
confidence: 69%
“…In addition to their antimicrobial properties, certain quinolones have significant immunomodulatory activities in vitro and in vivo (Dalhoff, 2005). A newly developed fluoroquinolone, garenoxacin mesilate hydrate (GRNX), has a low mutant prevention concentration (the concentration that prohibits the growth of mutants from a susceptible population of more than 10 10 cells) and a narrow mutant selection window (defined as the range between the minimum inhibitory concentration and the mutant prevention concentration, provides a means for defining the ability of an antibiotic to prevent the emergence of mutants) and is useful for minimizing the selection of quinolone-resistant mutants of pneumococcal strains (Yamamoto et al, 2009). However, the immunomodulatory properties of GRNX in human lung cells have not previously been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Determination of antimicrobial susceptibility is important, particularly when treatment has failed. According to studies, the level of resistance to quinolones in Asian countries, especially in the Middle East, is significantly higher than that in other parts of the world; quinolone resistance has been reported in Korea (6.1%), the Philippines (9.1%), and Hong Kong (14.3%) was reported, and the development of strains resistant to levofloxacin in Qatar, Kuwait, Lebanon raised serious concerns [12,13] . In addition, a research in southern Nigeria confirmed that the level of resistance to first-generation quinolones is relatively higher than that to third-generation quinolones, i.e., the highest resistance is to nalidixic acid and the least resistance is to levofloxacin [14] .…”
Section: Discussionmentioning
confidence: 99%